Implementation of Strategic Management in Improving Public Sector Organizational Performance - Usman, Asri; Alimuddin, Alimuddin; Albahrun, Yudi Basma; Ahmad, A. Ikhwanul; Kamal, Afrah Namirah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the roles of strategic management, management accounting, and Government Accounting Standards (SAP) in enhancing the performance of public sector organizations in Indonesia. The research employs a literature review approach by examining relevant national and international academic sources. The findings indicate that the implementation of strategic management strengthens policy effectiveness, cost efficiency, and public legitimacy. Management accounting plays a vital role in supporting data driven decision making, cost control, and performance based budgeting. Meanwhile, the adoption of accrual based SAP contributes to greater fiscal transparency, improved financial reporting quality, and stronger public accountability. However, the implementation of these three instruments continues to face challenges, including limited human resource capacity, bureaucratic resistance, and the suboptimal use of digital technologies. This study underscores that synergy among strategic management, management accounting, and SAP is essential for building transparent, efficient, and adaptive public governance that is responsive to societal needs.